Exploring the Role of Artificial Intelligence in Learning Media for Vocational Education: A Systematic Literature Review - Muttaqin, Muhammad Fuad; Sukrawan, Yusep; Rosyadi, Mohamad Iqbal (Universitas Ahmad Dahlan, 2024)
This article is a systematic literature review which aims to explore information about the use of artificial intelligence (AI) in learning media in vocational education. In the Industry 4.0 era, education needs to keep up with technological developments. AI has an important role in creating learning materials and solving problems in educational environments. AI is able to analyze individual learning styles and needs, providing personalized and relevant material. This research reveals that the use of artificial intelligence in vocational education has several important findings. These findings include personalization of learning based on individual learning styles and needs, engaging learning experiences through interactive simulations and educational games, as well as enriching practical experiences through virtual laboratories and industrial simulations. Additionally, the artificial intelligence assessment system is capable of detecting students' weaknesses and strengths in real-time, providing personalized feedback, and assisting in monitoring overall class performance. This research shows that artificial intelligence is not just a tool, but also a partner that drives innovation in vocational education, helps students reach their full potential, and prepares them for a bright future in their chosen industry.